PERSPEKTIF FIKIH EKONOMI TERHADAP PELAKSANAAN AKAD “UTANG PIUTANG” PADA PERBANKAN SYARIAH DI SUMATERA BARAT - SYUKRI ISKA (JURIS (Jurnal Ilmiah Syariah), 2016)
This study was purposed at identifying the various transactions in Islamic banking of West Sumatera were categorized on the “debts”; describing the implementation of the transaction; and analyzing the various transactions were based on the economic fiqh perspective. This study belongs to qualitative case study by using in-depth interviews as research instrument. The data were analyzed qualitatively based on the economic fiqh perspective, Al-Qur'an, Sunnah, Ijtihad the scholars, and the Fatwa of National Sharia Council (DSN) and Indonesian Council of Scholars (MUI). The results of this study revealed that the types of transactions were categorized “debts” was murabahah, qardh (bailout pilgrimage), hiwalah, and rahn (pawning gold). Murabahah was presented on all Islamic Bank but not all transactions on Islamic banking of West Sumatera based on the economic fiqh perspective such the calculation of the margin murabahah based on the amount of banks financing. Then the calculation of ujrah on the bailout pilgrimage was still based on the amount of bail. Furthermore, the calculation of ujrah on pawning gold was not based on the calculation of the treatment period but to the amount of “debt” funds. The conclusion was the implementation of the “debts” contract in Islamic banking of West Sumatera not run well as the economic fiqh perspective. Kata kunci: akad “utang piutang”, perpektif fikih ekonomi, perbankan syariah, Sumatera Barat